Analisis Penerapan Program Green School Dalam Menanamkan Nilai Karakter Peduli Lingkungan Di SD Inpres Borongunti Kecamatan Bajeng Kabupaten Gowa - Muhajir Muhajir; Ashar Ashar; Rahmatiah Rahmatiah (Journal on Education, 2024)
Rahmatiah, 2023. Analysis of the Implementation of the Green School Program in Instilling the Character Value of Environmental Care in Class III of SD Inpres Borongunti, Bajeng District, Gowa Regency. Thesis, Department of Elementary School Teacher Education, Faculty of Teacher Training and Education, Universitas Muhammadiyah Makassar. Supervisor I Dr. Muhajir, M.Pd and Supervisor II Dr. Ashar, S.Or., S.Pd., M.Pd. This type of research uses qualitative research. The data from this study are in the form of increasing the value of environmental care characters and the supporting and inhibiting factors of the green school program. This research goes through procedures that include observation, interviews, and documentation. The subjects in this study were students of SD Inpres Borongunti, Bajeng sub-district, Gowa Regency. The results showed that increasing the value of students' environmental care character by using the green school program can be carried out well, this can be seen from the creativity of students towards things that can damage the environment, for example waste recycling management. While the supporting factors for the green school program are from their own living environment as well as inhibiting factors.Judging from the results of the study, it can be concluded that the value of students' environmental care character greatly affects student creativity.